Anthropological crisis and education - Kadnikova, L. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article the crisis of education in the context of modern civilization crisis is discussed, and possible ways to overcome it by changing a number of fundamental principles of the education system are suggested.